2021
DOI: 10.1002/ehf2.13300
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in congestive markers in patients hospitalized for acute heart failure

Abstract: Aims We sought to examine sex differences in congestion in patients hospitalized for acute heart failure (AHF). Understanding congestive patterns in women and men with AHF may provide insights into sex differences in the presentation and prognosis of AHF patients. Methods and results In a prospective, two-site study in adults hospitalized for AHF, four-zone lung ultrasound (LUS) was performed at the time of echocardiography at baseline (LUS1) and, in a subset, pre-discharge (LUS2). B-lines on LUS and echocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition, many of the patients were too ill to collaborate to be in a seated position. All of this meant that we chose not to use a 12-zone LUS model which would otherwise have allowed us to assess the posterior zones and instead chose to only assess 8 zones (frontal and lateral zones) which limits our findings although the 8-zone model has been successfully used in several other studies [31,32]. However, several sensitivity analyses were carried out which confirmed our findings in the primary analyses.…”
Section: Strengths and Limitationsmentioning
confidence: 74%
“…In addition, many of the patients were too ill to collaborate to be in a seated position. All of this meant that we chose not to use a 12-zone LUS model which would otherwise have allowed us to assess the posterior zones and instead chose to only assess 8 zones (frontal and lateral zones) which limits our findings although the 8-zone model has been successfully used in several other studies [31,32]. However, several sensitivity analyses were carried out which confirmed our findings in the primary analyses.…”
Section: Strengths and Limitationsmentioning
confidence: 74%
“…Shim et al [ 37 ] demonstrated that women are more prone to develop arterial stiffness, and this was related to modification in the cardiac parameters of diastolic function. Espersen et al [ 17 ] partially confirmed these characteristics: women with AHF showed similar prevalence in jugular venous distension and crackles on auscultation while demonstrating reduced prevalence in lower extremity oedema. Although no differences were according to instrumental evaluations (lung ultrasound and chest X-rays), the authors pointed out lower values in BUN and creatinine in women than men [ 17 ].…”
Section: Discussionmentioning
confidence: 91%
“…Espersen et al [ 17 ] partially confirmed these characteristics: women with AHF showed similar prevalence in jugular venous distension and crackles on auscultation while demonstrating reduced prevalence in lower extremity oedema. Although no differences were according to instrumental evaluations (lung ultrasound and chest X-rays), the authors pointed out lower values in BUN and creatinine in women than men [ 17 ]. BUN and BUN/Cr ratio are reliable markers of neurohormonal activation and venous congestion [ 38 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…demonstrated that a score comprising B‐lines along with left ventricular ejection fraction and tricuspid annular plane systolic excursion provided additional prognostic value to the GRACE and TIMI risk scores for the combined endpoint of all‐cause death and nonfatal MI during a median follow up of 5 months. By contrast, in studies among patients with acute HF, B‐lines early during the admission (baseline) are typically less prognostically important for post‐discharge outcomes than B‐lines assessed prior to hospital discharge 16,17 . While all studies in this systematic review performed LUS examinations on admission, data on B‐line number prior to hospital discharge and their prognostic relevance for subsequent outcomes such as HF‐readmissions and mortality are lacking for patients with ACS.…”
Section: Discussionmentioning
confidence: 93%